2021
DOI: 10.1371/journal.pcbi.1009185
|View full text |Cite
|
Sign up to set email alerts
|

Neuron tracing and quantitative analyses of dendritic architecture reveal symmetrical three-way-junctions and phenotypes of git-1 in C. elegans

Abstract: Complex dendritic trees are a distinctive feature of neurons. Alterations to dendritic morphology are associated with developmental, behavioral and neurodegenerative changes. The highly-arborized PVD neuron of C. elegans serves as a model to study dendritic patterning; however, quantitative, objective and automated analyses of PVD morphology are missing. Here, we present a method for neuronal feature extraction, based on deep-learning and fitting algorithms. The extracted neuronal architecture is represented b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…Based on these observations, we used a model organism to determine whether 3TC may directly protect aging neurons. C. elegans PVD neurons serve as a model to study how dendritic morphology changes with aging (Yuval et al, 2021 ); here, we showed that the PVD neuron degenerates with aging, consistent with other reports that have linked this degeneration with immune sensor activation (Lezi et al, 2018 ), but that 3TC protects against this degeneration and preserves dendritic structure. Dendrites also degenerate with aging in most mammals (Furusawa & Emoto, 2021 ), and therefore, our results could suggest a neuron‐specific mechanism by which 3TC may improve cognitive function in mice.…”
Section: Discussionsupporting
confidence: 92%
“…Based on these observations, we used a model organism to determine whether 3TC may directly protect aging neurons. C. elegans PVD neurons serve as a model to study how dendritic morphology changes with aging (Yuval et al, 2021 ); here, we showed that the PVD neuron degenerates with aging, consistent with other reports that have linked this degeneration with immune sensor activation (Lezi et al, 2018 ), but that 3TC protects against this degeneration and preserves dendritic structure. Dendrites also degenerate with aging in most mammals (Furusawa & Emoto, 2021 ), and therefore, our results could suggest a neuron‐specific mechanism by which 3TC may improve cognitive function in mice.…”
Section: Discussionsupporting
confidence: 92%
“…The neurons are located between the hypodermis and its basement membrane. 38 The PVD neurons form a network of branches that envelop the body and tail of the nematode ( Figure 5 A). To investigate if A. flagrans infection can cause PVD neurodegeneration, the NC1686 C. elegans strain, where PVD neurons are visualized by GFP, was used in a fungal infection assay ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%